2020
DOI: 10.32859/era.19.50.1-12
|View full text |Cite
|
Sign up to set email alerts
|

Ethnobotanical survey of medicinal plants used in the treatment of kidney stones in Region of Fez-Meknes, Morocco

Abstract: Background: This survey was carried out in the prefecture of Fez-Morocco in order to establish an inventory of medicinal plants used in the treatment of urolithiasis pathology and to collect as much information as possible about the therapeutic uses and recipes reported by the local population.Methods: An ethnobotanical survey undertaken between January 2015 to December 2017 in the region of Fez-Meknes (Morocco) which includes the urban community of Fes-Medina, Hassan II University Hospital Center, and Sidi Hr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 8 publications
2
5
0
Order By: Relevance
“…2 .a). This finding was in agreement with other ethnobotanical studies ( Kabbaj et al, 2012 );( Ammor et al, 2020 ) . 69% of respondents prefer the use of modern medicine against cancer vs. 27 % prefer the use of herbal medicine.…”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…2 .a). This finding was in agreement with other ethnobotanical studies ( Kabbaj et al, 2012 );( Ammor et al, 2020 ) . 69% of respondents prefer the use of modern medicine against cancer vs. 27 % prefer the use of herbal medicine.…”
Section: Resultssupporting
confidence: 93%
“…Fez-Meknes region- Morocco is among the most recognized region in the country for use of traditional herbal medicine against diseases and, therefore, was selected for being a study area ( Jouad et al, 2001 ); ( Ammor et al, 2020 ).…”
Section: Methodsmentioning
confidence: 99%
“…These findings are in agreement with those previously reported in different neighboring regions ( Benarba et al, 2015 ; Bouasla and Bouasla, 2017 ; Chaachouay et al, 2020 ). Besides these species, Parietaria officinalis L. was found to possess an FL of 100% for kidney diseases which is consistent with findings previously reported in North-West Algeria ( Benarba, 2016 ) and Morocco ( Ammor et al, 2020 ). Inconsistent with our previous findings in both North-West ( Benarba et al, 2015 ) and South-West Algeria ( Benarba, 2016 ), T. vulgaris was the only species having the highest FL of 100% for skin diseases.…”
Section: Discussionsupporting
confidence: 90%
“…Regarding, these ancestral medical practices in this country, we found that there are many investigations carried out in different regions of Morocco that deal with traditional use of medicinal plants for the treatment of renal diseases. In fact, an ethnobotanical survey conducted in the Fez-Meknes region was able to document traditional knowledge related to the 69 plant species belonging to 38 families, used as traditional remedies for the treatment of kidney diseases in this region [8]. In the Boulemane region of Morocco, Jouad et al (2001) conducted an ethnobotanical survey to document traditional medicinal practices related to medicinal plants used for the treatment of diabetes and kidney disease, among which they identify 33 medicinal plants used specifically to treat kidney problems [9].…”
Section: Introductionmentioning
confidence: 99%